(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Wireless communication has become a basic utility in our day to day life such that it becomes a fundamental of our lives and this communication uses the radio spectrum for data transfer. There are issues in using the radio spectrum they are capacity, efficiency, availability and security. The usage of Wi-Fi also causes damage to the ecosystem such as flora and fauna.The defects of the Wi-Fi technology has given birth to the concept of Li-Fi (Light Fidelity) technology. Li-Fi is an advanced technology. This project is concise to vehicle to vehicle communication for avoiding road accidents. We use the ultrasonic sensor, gas sensor, vibration sensor, LCD display, LiFi transmitter and receiver. In case of an abnormal condition in the front vehicle, the vehicle at the back will be intimated and will stop on the second. For future enhancement, Li-Fi can be implemented in class rooms where data stored in the server is transmitted through LED lights attached in the ceilings of the classroom and the data can be received through Li-Fi receiver(dongle) which is present with each student in the classroom.